EU ENLARGEMENT TO THE EAST AND ITS IMPACT ON NON-ACCESSION COUNTRIES. GENERAL EQUILIBRIUM APPLIED ANALYSIS - Eremenko, Igor (Journal of European Economy, 2002)
The results and consequences of the EU enlargement to the East are investigated, especially is emphasized the impact it has on trade flows of the CEE countries. The model experiments are analyzed, i. e. Computable General Equilibrium Model is employed, and the database is aggregated into 5 regions and 8 sectors of economy. Besides, the concept of the effect of technological gap between the FSU and other countries is introduced.